ISOLASI DAN IDENTIFIKASI SAPONIN DARI ALOE BARBADENSIS MILLER SEBAGAI ANTIBIOTIK ALAMI : PENANGGULANGAN MASTITIS PADA SAPI PERAH - Imbang Dwi Rahayu (Jurnal Gamma, 2009)
The mastitis in dairy cattle is caused by Staphylococcus aureus. The bacteria are multiresistantto antibiotic. Isolated of Aloe barbadensis Miller, that has antibacterial, saponin is needed to replacesynthetic antibiotic. The research has conducted to tested antibacterial activity of saponin for thegrowth of Staphylococcus aureus.Saponin was exstracted from gel of Aloe vera leafs by 95% ethanol, 50% ethanol and nbutanol.Isolated of saponin used to the Coulom Cromatography and Thin Layer Cromatography. Itneeds “Liebermann-Burchad” reagent, acetic anhidryde and sulfuric acid (1:1:1:1) for identifyingof saponin. These saponin preparation were detected by short wave U.V lamp on silica gel G platesdeveloped with solvent of butanol-ethanol-water (2 : 4: 4). The saponin’s powder was produced bydrying process, amylum or dexstrin as kinds of filler. The ratio of saponin and dexstrin was 80% :20%. Six levels of saponin were used in experiment i.e : 1,5%; 3,0%; 6,2%; 12,5%; 25% and 50%.The parameters of the research were Minimum Inhibition Concentration (MIC) and cakram disk.The result of experiment was analysed with descriptively, penicillin was used as positive control.The saponin’s powder give antibacterial activity that higher than saponin’s concentrated. Therewere similarity in antibacterial activity between the saponin’s powder was added dextrin withpenicillin.